2018
DOI: 10.1038/s41467-018-05421-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity across trophic levels drives multifunctionality in highly diverse forests

Abstract: Human-induced biodiversity change impairs ecosystem functions crucial to human well-being. However, the consequences of this change for ecosystem multifunctionality are poorly understood beyond effects of plant species loss, particularly in regions with high biodiversity across trophic levels. Here we adopt a multitrophic perspective to analyze how biodiversity affects multifunctionality in biodiverse subtropical forests. We consider 22 independent measurements of nine ecosystem functions central to energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
188
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 229 publications
(201 citation statements)
references
References 68 publications
(110 reference statements)
11
188
1
1
Order By: Relevance
“…As smaller patches have lower species numbers, the loss of species should have more pronounced effects on ecosystem functioning in such patches. Such shifts in multitrophic diversity have consequences for functioning (Schuldt et al 2018). At the level of single ecosystem functions, we did not find a consistent trend toward positive interaction effects, with positive interactions for some functions, and negative interactions or no trend for others.…”
Section: Discussioncontrasting
confidence: 84%
“…As smaller patches have lower species numbers, the loss of species should have more pronounced effects on ecosystem functioning in such patches. Such shifts in multitrophic diversity have consequences for functioning (Schuldt et al 2018). At the level of single ecosystem functions, we did not find a consistent trend toward positive interaction effects, with positive interactions for some functions, and negative interactions or no trend for others.…”
Section: Discussioncontrasting
confidence: 84%
“…This has yet hardly been shown when optimizing for multiple ES. In addition, previous studies have found that maintaining multiple ES is best supported by heterogeneity, for example through diversity in forest species and plant functional traits (Felipe‐Lucia et al, ; Schuldt et al, ). This finding applies also for the landscapes scale, when various LULC types provide different ES to different extents (Plas et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Forests play a central role in hosting global terrestrial biodiversity and providing important ecosystem services, such as carbon sequestration or timber production (FAO 2010;Watson et al 2018). This role, however, can be critically altered by ongoing dramatic global declines in biodiversity (IPBES 2019), as biodiversity has been demonstrated to enhance forest multifunctionality (Gamfeldt et al 2013;van der Plas et al 2016;Schuldt et al 2018). During the last decade, numerous studies provided evidence for a positive net biodiversity effect on primary productivity (overyielding) in forests (Morin et al 2011;Paquette & Messier 2011;Zhang et al 2012;Liang et al 2016;Tobner et al 2016;Grossman et al 2017;Fichtner et al 2018;Huang et al 2018).…”
Section: Introductionmentioning
confidence: 99%